Dynamics of Clomazone Formulations Under Different Applications Conditions - TROPALDI,L. (2019)
ABSTRACT: Maintenance of straw on the soil surface in sugarcane production areas can influence weed occurrence and herbicide dynamics. After application, considerable losses of clomazone can occur as a result of its physicochemical characteristics. For this reason, novel formulations have been developed. In addition to the conventional formulation, microencapsulated formulations are currently available. Thus, the aim of this study was to observe and compare the effect of clomazone formulations under different application conditions. For this purpose, the experiment was carried with 12 treatments in a completely randomized design, with four replications, using clomazone formulations (1,200 g a.i. ha-1), on soils with different moisture levels, in the presence and absence of sugarcane straw, followed or not by rainfall simulation. The treatments were compared by observation of number of emerged plants and phytotoxicity at 7 and 14 DAA, as well shoot dry matter at 14 DAA for Ipomoea nil, Urochloa decumbens and Panicum maximum. In general, the microencapsulated formulation presented a better performance under the less suitable application conditions when compared to the conventional one. However, for the other conditions, both formulations had a similar performance.